The relationship between bacterial characteristics and mortality in diabetic foot ulcers' patients admitted to Dr. H. Abdul Moeloek General Hospital, Lampung - Iswandi Darwis; Gusti Ngurah P Pradnya Wisnu; Sekar Mentari (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACT Around 25% of people with diabetes experience diabetic foot ulcers in their lives, accompanied by infections due to various types of bacteria. Infection due to Gram-negative and Gram-positive bacteria are reported to have different inflammation patterns, where the latter being reported to have a higher mortality rate. This study was an analytic observational study with a cross-sectional design to determine the relationship between bacterial characteristics and mortality in diabetic foot ulcers. Data were obtained from medical records of diabetic ulcer patients admitted to Dr. H. Abdul Moeloek General Hospital, Lampung, in 2017–2020. There were 131 diabetic foot ulcers patients identified, with the median age of the subjects was 53 years, 43.5% of the subject were male, and 56.5% were female. The mean hemoglobin was 9.3 g/dl, WBCs were 19.0 ×103/ml, and platelets were 422.1 ×103/ml. The mean length of stay in the hospital was 10.7 days. Eighteen subjects died during the hospital stay, with 15 of them were from the Gram-negative monomicrobial group. The results of the Fischer Exact test on mortality and bacterial characteristics among monomicrobial infections (p=0.688) indicate no relationship between the characteristics of the infectious pathogen and mortality in diabetic foot ulcers. Keywords: bacteria, diabetes, diabetic foot ulcers, mortalityCorrespondence: iswandi.darwis@gmail.com